Perceptions of the Implementation of Free Nutritious Meals Using Local Government Budget Funds in Penajam Paser Utara Regency - Indrayani, Indrayani (IJBLE Scientific Publications Community Inc., 2025)
This study aims to analyze the perceptions of the community and stakeholders regarding the implementation of the Free Nutritious Meal Program (MBG) funded by the Regional Budget (APBD) in Penajam Paser Utara Regency. The research approach used is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation of key informants, including school principals, teachers, and Education Office officials. The results show that, in general, the informants have a positive perception of the MBG Mandiri program as a strategic policy of the local government in improving the nutritional quality of students and supporting the achievement of human development goals. This program is considered to have a direct impact on increasing student motivation, participation, and awareness of the importance of healthy eating in the school environment. However, the implementation of the program still faces several obstacles, such as limited healthy kitchen facilities, human resource readiness, and differences in managerial capabilities between schools. In addition, the effectiveness of the program is highly dependent on the transparency of APBD management, cross-sector coordination, and active community participation. Therefore, it is necessary to strengthen governance, increase the capacity of implementers, and establish a sustainable evaluation mechanism so that the MBG Mandiri program can run more effectively and sustainably. The results of this study are expected to provide input for local governments in formulating more participatory and equitable public policies in the field of school children's nutrition.